Financial fraud prevention and detection : governance and effective practices - Young, Michael R. (Hoboken, New Jersey : Wiley, 2014)
"Step-by-step guidance for board members and executives on preventing and detecting accounting fraudIn the wake of highly publicized allegations of accounting irregularities and fraudulent financial reporting that are shaking up today's corporate community, Financial Fraud Prevention and Detection provides a step-by-step guide to how these crises can envelop a company and how to prevent them from happening in the first place. It is written for almost everyone involved: outside directors, audit committee members, senior executives, CFOs, CPAs, in-house lawyers, and outside law firms. Provides a blueprint for Fraud Prevention and Detection for corporate executives Presents step-by-step guidance to corporate boards and C-suite executives on managing the threat of accounting fraud Prepares directors and executives for the possibility of accounting irregularities Answers the question of how accounting fraud starts--and grows With solid strategies for prevention of accounting fraud as well as a process to follow when fraud has been discovered, Financial Fraud Prevention and Detection vividly explores the corporate environment that causes fraud, how it spreads, the kind of cries it can create for a company, and the best ways to deal with it"--
pt. I. Origin -- pt. II. Prevention -- pt. III. Detection -- pt. IV. The future.
Print version record and CIP data provided by publisher.
Keywords: Accounting fraud -- United States; Corporations -- Accounting -- Corrupt practices -- United States; Corporations -- Accounting -- Corrupt practices -- United States -- Prevention; Corporate governance -- United States; Commercial crimes -- United States; BUSINESS & ECONOMICS -- Accounting -- Financial; Accounting fraud; Commercial crimes; Corporate governance; Corporations -- Accounting -- Corrupt practices; Corporations -- Accounting -- Corrupt practices -- Prevention; United States; Electronic books